Man-eaters - Hopping, Lorraine Jean.; Egan, Christopher (New York : Trumpet Club, 1992)
Introduces the characteristics, habits, and environment of various species of meat-eating predators.
Keywords: Dangerous animals -- Juvenile literature; Dangerous animals